Ochrona sądowa w postępowaniach dyscyplinarnych lekarzy. Analiza orzeczeń kasacyjnych Sądu Najwyższego - Wrześniewska-Wal, Iwona (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article discusses the cassation institution in disciplinary cases of doctors. The basic differences between this cassation and the cassation provided for by the Code of Criminal Procedure are indicated. Due to the deontology of the disciplinary proceedings of doctors, there is no doubt that in the light of the Constitution it is permissible and even unavoidable to form such a model of conduct control on the professional liability of physicians, which provides for derogations from the standards in force in criminal procedure sensu stricto. The analysis of Supreme Court case law in disciplinary cases of doctors in terms of effective court protection takes into account the cassations of the years 2011-2016.